2004
DOI: 10.1016/j.jacc.2004.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between stress-induced myocardial ischemia and atherosclerosis measured by coronary calcium tomography

Abstract: Ischemic MPS is associated with a high likelihood of subclinical atherosclerosis by CAC, but is rarely seen for CAC scores <100. In most patients, low CAC scores appear to obviate the need for subsequent noninvasive testing. Normal MPS patients, however, frequently have extensive atherosclerosis by CAC criteria. These findings imply a potential role for applying CAC screening after MPS among patients manifesting normal MPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
248
1
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 406 publications
(274 citation statements)
references
References 42 publications
15
248
1
10
Order By: Relevance
“…Several studies have shown that the coronary artery calcium score is valuable in identifying patients with a high likelihood of inducible myocardial ischemia (59,60). These studies have consistently observed that the likelihood of ischemia in patients with a calcium score Ͻ100 is negligible, whereas those with a score of Ն400 have a relatively high likelihood of inducible ischemia.…”
Section: What Tests or Sequence Of Tests Should Be Considered? Withmentioning
confidence: 99%
“…Several studies have shown that the coronary artery calcium score is valuable in identifying patients with a high likelihood of inducible myocardial ischemia (59,60). These studies have consistently observed that the likelihood of ischemia in patients with a calcium score Ͻ100 is negligible, whereas those with a score of Ն400 have a relatively high likelihood of inducible ischemia.…”
Section: What Tests or Sequence Of Tests Should Be Considered? Withmentioning
confidence: 99%
“…A number of studies have explored the relationship between CAC scoring and myocardial perfusion imaging (MPI). Among them, one study including low risk patients showed that only 2% of patients with CAC <100 have abnormal MPI studies, compared to 31% of patients with CAC >400 (27,28). A CAC score ≥709 has been suggested as the optimal cutoff for detecting CAD missed by SPECT imaging, improving the sensitivity of SPECT from 76% to 86% (29).…”
Section: Mini-reviewmentioning
confidence: 99%
“…That is, the prevalence of inducible ischemia was low for CAC scores of less than 100 but increased dramatically for higher CAC scores. In one large observational series, the rate of inducible ischemia approached 20% for patients with CAC scores of $400 (16). The frequency of inducible ischemia is elevated in diabetic patients, patients with metabolic syndrome, and patients with a family history of premature CAD at a lower threshold-CAC scores of $100.…”
Section: Added Value Of Determination Of Coronary Calcium With Stressmentioning
confidence: 99%